(3GdJfXje GdbGfhfj ddJLGQI hGdEKHGJ GdEdcJQhfj aj GdYGdes - (3eMeO NGdO LeGd(B, (3QSJes ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2006)
(3jVe GdJfXje GdbGfhfj ddJbGYO Yf HYO, GdMeGjI GdbGfhfjI dfXe GdeYdheGJ hGdJHGOdGJ GdGdcJQhfjI aj GdOhd GdYQHjI, GdJhbjY GdGdcJQhfj aj SWhQ, GbJQGM GMcGe GdeYGedGJ GdGdcJQhfjI GddHfGfj, eTQhY GdbGfhf GddHfGfj Mhd GdGKHGJ HGdhSGFW GdGdcJQhfjI, GbJQGM bGfhf eJYdb HGdJhGbjY GdGdcJQhfjI GddHfGfH, GbJQGM bGfhf GdeJYdb HGdJhbjY hGdSfOGJ GdGdcJQhfjI GddHfGfj(B.s
(3HjHdjhZQGajG(B: (3U(B.521s
Keywords: (3GdJLGQIs; (3GdJfXjes; (3GdbGfhf GdJLGQjs